Seroprevalence of anti-SARS-CoV-2 specific antibodies in vaccinated and vaccine naïve adult Nigerians. - Abdulfattah Adekunle Onifade; Adeola Fowotade; Sheu Kadiri Rahamon; Victory Fabian Edem; Surajudeen Adebayo Yaqub; Olatunji Kadri Akande; Olatunbosun Ganiyu Arinola (PLoS ONE, 2023)
Background Reports on the evaluation of immune responses to different COVID-19 vaccines are limited. Similarly, effects of age and gender have not been well explored as variables that could impact on the vaccine-induced antibody response. Therefore, seroprevalence of anti-SARS-CoV-2 specific antibodies in vaccinated and vaccine naïve adult Nigerians was determined in this study. Methodology A total of 141 adults were enrolled into this study. Presence or absence of SARS-CoV-2 infection was confirmed by real-time reverse-transcriptase polymerase-chain reaction (RT-PCR) assay on nasopharyngeal and oropharyngeal swab specimens. Anti-SARS-CoV-2 Specific IgG and IgM antibodies were qualitatively detected using a Rapid Diagnostic Test kit. Results Pre-vaccination, 77% of the study participants had never had PCR-confirmed COVID-19 test yet 66.7% of them were seropositive for SARS-CoV-2 antibodies. Of 111 COVID-19 vaccinated participants, 69.2% and 73.8% of them had SARS-CoV-2 specific IgG post-first and second doses of COVID-19 vaccine respectively. However, 23.1% and 21.4% of the participants who have had first and second doses respectively had no detectable anti-SARS-CoV-2 antibodies. The proportion of participants with SARS-CoV-2 specific IgG was insignificantly higher in those between the ages of 18-40 years and 41-59 years compared with individuals aged ≥60 years. No significant association was observed between gender and seropositivity for SARS-CoV-2 antibodies. Conclusion There is high SARS-CoV-2 antibody seroprevalence among Nigerian adults who never had PCR-confirmed COVID-19. Also, there is the need for anti-SARS-CoV-2 antibodies screening post vaccination as this could be essential in achieving herd immunity. Age and gender do not seem to have significant association with seropositivity.